PENENTUAN TIPE FLUIDA DAN GUGUS FUNGSI MANIFESTASI PANAS BUMI KAWAH TUA GUNUNG API SOPUTAN - Ronaldo J. Toar; Donny Royke Wenas; Theresje Mandang (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
Indonesia is a country that has the largest geothermal resources in the world which is directly proportional to the number of volcanoes. Indonesia is an archipelagic country located at three junction of active mountain plates, namely the Eurasia, Indo-Australia and Pacific plates. Where Indonesia is also located in an active ring of fire that is associated with active volcanoes in Indonesia. North Sulawesi is one of the provinces in Indonesia which has several active volcanoes, one of which is the object of research is Mount Soputan. This volcano is located in South Minahasa and Southeast Minahasa Districts, North Sulawesi Province. The method used in this research is descriptive method and analysis of geothermal fluid chemical data. Analysis of the ion content in the fluid using a SpectroDirect Photometer. As well as functional group analysis using the FTIR Spectroscopy method (Fourier Transform Infra Red), this method is an infrared spectroscopy method equipped with Fourier transform for its spectrum analysis. Geothermal manifestation fluid in the Old Crater of Mount Soputan Volcano is a bicarbonate type of fluid with an HCO3 content of 479 ppm. The high HCO3 content is thought to be associated with the increase in geothermal fluids containing gas, especially CO2, which then experiences condensation in shallow aquifers.